Training health professionals in shared decision making: Update of an international environmental scan. Issue 11 (November 2016) - Diouf, Ndeye Thiab; Menear, Matthew; Robitaille, Hubert; Painchaud Guérard, Geneviève; Légaré, France
Highlights: In 4 years, 94 new SDM training programs were identified. Interest in SDM training is spreading to new parts of the world. There is a new interest in opening programs to patient participation. Interprofessional collaboration still seems neglected. Few programs are rigorously evaluated. Abstract: Objective: To update an environmental scan of training programs in SDM for health professionals. Methods: We searched two systematic reviews for SDM training programs targeting health professionals produced from 2011 to 2015, and also in Google and social networks. With a standardized data extraction sheet, one reviewer extracted program characteristics. All completed extraction forms were validated by a second reviewer. Results: We found 94 new eligible programs in four new countries and two new languages, for a total of 148 programs produced from 1996 to 2015—an increase of 174% in four years. The largest percentage appeared since 2012 (45.27%). Of the 94 newprograms, 42.55% targeted licensed health professionals (n = 40), 8.51% targeted pre-licensure (n = 8), 28.72% targeted both (n = 27), 20.21% did not specify (n = 19), and 5.32% targeted also patients (n = 5). Only 23.40% of the new programs were reported as evaluated, and 21.28% had published evaluations. Conclusions: Production of SDM training programs is growing fast worldwide. Like the original scan, this update indicates that SDM training programs still vary widely. Most still focus on the single provider/patient dyad and few are evaluated. Practice implications: This update highlights the need to adapt training programs to interprofessional practice and to evaluate them.